ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH: PERSPEKTIF KABUPATEN/KOTA - Tarisa Azzahro; Maria Maria; Sulaiman Sulaiman (Jurnal Riset Terapan Akuntansi, 2026)
The purpose of this study is to investigate the differences between South Sumatra and Lampung's regency and city governments' financial performance. Numerous metrics, including ratios that show the level of fiscal decentralisation, dependency, efficiency, effectiveness, and regional financial independence, will be used to evaluate this. All Budget Realisation Reports (LRA) for both regency and municipal governments in these provinces are included in the study's population. The LRAs in the sample span the years 2019 through 2023. According to the analysis, regional financial performance for 2019-2023 shows that Palembang City has better financial performance, with a high level of independence and low dependency. While fiscal decentralization is relatively good in some cities, efficiency remains fluctuating and the effectiveness of local revenue (PAD) is uneven. Therefore, regions need to increase local revenue (PAD), increase efficiency, and reduce dependence on the central government to become more independent. Keywords: Regional Financial Independence Ratio, Degree of Fiscal Decentralization Ratio, Dependency Ratio, Efficiency Ratio, Effectiveness Ratio of PAD.